2006
DOI: 10.1099/vir.0.81485-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an allelic variant of the goat PrP gene associated with resistance to scrapie

Abstract: The association between PrP gene variations and scrapie susceptibility was studied in a single herd of Ionica breed goats. The entire herd comprised 100 animals, 11 of which were clinically affected and showed pathological prion protein (PrP Sc ) deposition in both their central nervous system (CNS) and lymphoreticular system (LRS). Among asymptomatic goats, nine harboured PrP Sc in both CNS and LRS, 19 showed PrP Sc only at the LRS level and 61 animals had no PrP Sc deposition. Genetic analysis of the PrP gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
130
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(146 citation statements)
references
References 35 publications
9
130
1
6
Order By: Relevance
“…Later, Vaccari et al (2006) and encourages positive selection for the ARR allele. The use of rams in risk groups R1, R2 and R3 is not restricted.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Vaccari et al (2006) and encourages positive selection for the ARR allele. The use of rams in risk groups R1, R2 and R3 is not restricted.…”
Section: Discussionmentioning
confidence: 99%
“…A PrP variant with three repeats and an additional W102G polymorphism was also associated with longer incubation periods after experimental challenges [33]. Polymorphisms with some resistance (low risk) association to scrapie are H143R, N146S/D, R154H and Q222K [3,11,74,92] [5] implies that the mechanisms underlying the interactions between PrP and agent are the same in different species, therefore highlighting the fact that it ought to be possible to establish general rules for PrP genetics. We may therefore deduce for example that R143 in sheep will also have a low risk association.…”
Section: Scrapie In Goatsmentioning
confidence: 99%
“…Codon 177 (Asn or Thr) is in the neighbourhood of codon 171 which again is associated with scrapie. Codon 226 (Gln or Glu) is adjacent to codon 225, which has been associated with CWD susceptibility [53] and close to codon 222, which is proposed to enhance resistance to scrapie in goats [3,92]. It remains to be seen whether these differences can give some protection for the transmission of TSE between species.…”
Section: Species Differences In Prp Sequencementioning
confidence: 99%
“…While the presence of asparagine instead of Serine or Aspartic acid at codon 146 has been found to be related to susceptibility to natural infection [78], it also has reported that the presence of Serine as heterozygous at the same codon has associated with the extended incubation period in oral challenging [90]. According to the results of various studies, arginine-histidine dimorphism at codon 154 has provided limited resistance [78,80,83,89]. The presence of glutamine/arginine as heterozygous at codon 211 has been found to Abbreviations of the amino acids: A, alanine; D, aspartic acid; F, phenylalanine; G, glycine; H, histidine; I, isoleucine; K, lysine; L, leucine; M, methionine; N, asparagine; P, proline; Q, glutamine; R, arginine; S, serine; T, threonine; V, valine; W, tryptophan.…”
Section: Resistance In Goatsmentioning
confidence: 99%